2018
DOI: 10.5217/ir.2018.16.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal amyloidosis secondary to ulcerative colitis

Abstract: Amyloidosis is defined as the extracellular deposition of non-branching fibrils composed of a variety of serum-protein precursors. Secondary amyloidosis is associated with several chronic inflammatory conditions, such as rheumatologic or intestinal diseases, familial Mediterranean fever, or chronic infectious diseases, such as tuberculosis. Although the association of amyloidosis with inflammatory bowel disease is known, amyloidosis secondary to ulcerative colitis (UC) is rare. A 36-year-old male patient with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Amyloid deposits in the gastrointestinal tract can cause acute obstruction or significant bleeding. Depending on the location in the intestine, amyloid can also cause abdominal pain, nausea, malabsorption and chronic diarrhoea [72].…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%
“…Amyloid deposits in the gastrointestinal tract can cause acute obstruction or significant bleeding. Depending on the location in the intestine, amyloid can also cause abdominal pain, nausea, malabsorption and chronic diarrhoea [72].…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%
“…Adalimumab (ADA) is a completely human anti-TNFα antibody and is licensed for the treatment of IBD [54][55][56][57][58]. Adalimumab was used in one case as a first-line biologic treatment and resulted in an improvement in proteinuria and renal function [34], but after infliximab's loss of response, adalimumab was found to be ineffective [3,36,38]. In clinical practice, azathioprine or methotrexate combination therapy increases efficacy and decreases immunogenicity, although combination therapy must be balanced against a potential rise in adverse events over time.…”
Section: Discussionmentioning
confidence: 99%
“…There are several tools for amyloid typing, including immunofluorescence, immunohistochemistry, immunoelectron microscopy, and proteomic studies [14,46]. Unfortunately, amyloid typing was not used in 11 reported cases [3,23–29,32,35,36,38]. We found that AA amyloidosis may be accompanied by other related disorders beside IBD, such as arthropathy or arthritis, which was the most reported disorder [3,22,26,29,34], FMF [3], or other extraintestinal manifestations [3,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For severe malabsorption, total parenteral nutrition may be useful if dysmotility-related symptoms are disabling, and the patient becomes malnourished. 31…”
Section: Malnutrition and Unintentional Weight Lossmentioning
confidence: 99%